Contribuição da extensão para a construção do guia PMBOK® para o planejamento de médio prazo - Angelim, Vanessa Lira; Barros Neto, José de Paula (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The Project Management Body of Knowledge (PMBOK®) guide brings together best practices for project management and edited an extension called Construction Extension to the PMBOK® Guide. The medium-term planning level (MTL) is one of the hierarchical levels of the Last Planner System (LPS®) and involves the process of constraint analysis. The present work sought to analyze the contributions of the extension for the construction of the PMBOK® guide for the MTL with the objective of identifying important practices that support the realization of the MTL in the construction. The interactions and contributions of the twelve areas of knowledge of the extension of the PMBOK® guide in the construction with the MTL were pointed out. It was noted that the scope of the MTL permeates and interacts with the management of the twelve areas of knowledge defined by the extension of the PMBOK® Guide in construction. The MTL incorporates actions present in some areas of knowledge or receives input data from others to feed the MTL. The contributions of this paper were to add other categories of constraints to be managed in PMP and to highlight integrated change control and risk management in PMP.